1991
DOI: 10.1093/bja/66.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxaemia During Anaesthesia—an Observer Study

Abstract: We have investigated 296 inpatients in a single-blind observer study to determine the incidence, degree and duration of hypoxaemia during anaesthesia. The clinical recognition of hypoxaemia, period of time until recognition and risk factors were studied. Oxygen saturation (Spo2) was monitored continuously with a pulse oximeter (Ohmeda, model 3700). One or more episodes of mild hypoxaemia (Spo2 86-90%) were recorded in 53% of patients. Severe hypoxaemia with Spo2 values less than 81% were recorded in 20% of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
19

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(68 citation statements)
references
References 24 publications
2
47
0
19
Order By: Relevance
“…In our study, all three episodes of desaturation were associated with hypotension, similar to the study by Siriussawakul et al who reported that nine out of twelve events were attributed to intraoperative hypotension and the other three due to sedatives administration (10). In contrast, a much higher incidence of desaturation following regional anaesthesia (75-87%) was seen in studies involving non-obstetric surgeries (18,19). This could be attributed to an older population age-group with more co-morbidities, and a more liberal use of sedative medications pre-and intraoperatively.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, all three episodes of desaturation were associated with hypotension, similar to the study by Siriussawakul et al who reported that nine out of twelve events were attributed to intraoperative hypotension and the other three due to sedatives administration (10). In contrast, a much higher incidence of desaturation following regional anaesthesia (75-87%) was seen in studies involving non-obstetric surgeries (18,19). This could be attributed to an older population age-group with more co-morbidities, and a more liberal use of sedative medications pre-and intraoperatively.…”
Section: Discussionsupporting
confidence: 90%
“…This may result in decreased oxygenation of blood. [1][2][3] A major cause of this derangement appears to be atelectasis, 4 which cannot be seen on conventional chest x-ray, 5 but was demonstrated by computed tomography (CT) of the chest. [6][7][8] Atelectasis in turn causes pulmonary shunt.…”
mentioning
confidence: 99%
“…The technical details of this sensor have been described in a previous publication [7]. Also, an identical (optical and electrical) foot PPG sensor was also developed in order to provide PPG comparison 2 studies between the two sites. A dual channel PPG processing system was also developed to detect and preprocess all acquired PPG signals (fontanelle and foot) simultaneously [7].…”
Section: Methods a Instrumentationmentioning
confidence: 99%
“…The technique relies on the presence of adequate peripheral arterial pulsations, which are detected as photoplethysmographic signals (PPG). When peripheral perfusion is poor, as in states of hypovolaemia, hypothermia, vasoconstriction, and low cardiac output, seen typically in meningococcal septicaemia, oxygenation readings become extremely unreliable or cease [1][2][3][4]. The problem arises because conventional sensors must be attached to the most peripheral parts of the body, such as the finger or toe, where pulsatile flow is most easily compromised.…”
Section: Introductionmentioning
confidence: 99%